Implementasi Bina Pribadi Islami Dalam Menumbuhkan Karakter Religius Dan Relevansinya Dengan Dimensi Profil Pelajar Pancasila (Studi Kasus di MTs Terpadu Nurul Amal Parang Islamic boarding School) - Siti Zumafidoh (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
This study aims to describe the implementation of the Islamic Character Development Program (BPI) in enhancing students' religious character and to analyze its relevance to the dimensions of the Pancasila Student Profile, particularly in the aspects of faith, devotion to God Almighty, and noble character. The BPI program is a guidance activity integrated into daily life within the dormitory environment of MTs Nurul Amal Boarding School, encompassing daily worship practices, habituation of noble character, and spiritual mentoring by teachers and supervisors. This research employs a qualitative approach using a case study method. Data were collected through observation, in-depth interviews with the school principal, BPI supervisors, and students, as well as program documentation. Data analysis was conducted using a descriptive-qualitative technique through data reduction, data display, and conclusion drawing. The findings indicate that the BPI Program has a significant impact on shaping students’ religious character, as reflected in improved worship discipline, respectful behavior, personal responsibility, and other positive habits. The program shows strong relevance to the dimensions of the Pancasila Student Profile, particularly in fostering spiritual values, ethics, and personal integrity. Thus, the BPI Program not only contributes to strengthening religious character but also supports the development of a student profile that balances Islamic values with national identity